ABDUVAHOB IBODIY'S VIEWS ON THE FIELD OF EDUCATION IN THE LITERARY ENVIRONMENT OF KOKAND IN THE EARLY 20TH CENTURY - Shakhnoza Abidovna Mirzamidinova (Bright Mind Publishing, 2025)
Events such as the termination of the Kokand Khanate by the Tsarist Empire much earlier than other khanates and emirates, i.e. in 1876, as well as the extreme strengthening of national oppression against the local population in the country, the assimilation of the nation’s genetics, forced the country’s intelligentsia to think deeply about the future, to be able to foresee and analyze what was being done by the colonial government.
Keywords: Czar empire, modern schools, innovative schools, nogay schools, material and technical base